MAPUCHE AUTONOMY (1907-1992). RENEWS OF AN OLD TRUNK - Ruiz Rodríguez, Carlos (Revista de Historia Social y de las Mentalidades, 2025)
Starting from the historiographical matter, “when the idea of autonomy appears for the Mapuche and how it is developed through the tim e?”. We start a search to the presence of the thought and the action of the autonomist Map uche along the post reduction period. This will allow us to know how the concept of auton omy started to be used among the Mapuche people, and also how this idea is becomin g in a strong concept that belongs to demands of the different segments of the Mapuche p eople in the present. The Mapuche demands of autonomy came from ancient t imes in the history of this people and this idea was developing since the decad e of 1970